Macular Pigment and Its Contribution to Vision - Loskutova, Ekaterina (MDPI, 2013)
Three dietary carotenoids, lutein (L), zeaxanthin (Z) and meso-zeaxanthin (MZ) accumulate at the central retina (macula), where they are collectively referred to as macular pigment (MP). MP’s pre-receptoral absorption of blue light and consequential attenuation of the effects of chromatic aberration and light scatter are important for optimal visual function. Furthermore, antioxidant activity of MP’s constituent carotenoids and the same blue light-filtering properties underlie the rationale for its putative protective role for age-related macular degeneration (AMD). Supplementation with L, Z and MZ augments MP and enhances visual performance in diseased and non-diseased eyes, and may reduce risk of AMD development and/or progression.